Revealing observatory networks through object stories: Introduction - Rebekah Higgitt (Science Museum Group Journal, 2023)
This paper introduces a group of three articles that bring together object stories relating to observatory history and networks. The three articles (‘Instrumental networks’, ‘Object itineraries’ and ‘Observatory audiences’) each bring together three object stories by different authors that contribute to the article theme. Here the genesis of the collection at the workshops of the Observatory Sites and Networks project is discussed, along with the approaches taken and the kind of insights that studies of material culture can shed on histories of observatories and the observatory sciences. The arrangement of the stories into three themes is outlined while common threads and recurring motifs that create connections and synergies across the thematic sections are highlighted. Together the collected papers make an argument for the use of objects in research, demonstrating the fruitfulness of investigating their histories and showing how they can expand our understanding of the networks of people, organisations and objects that were interested in or essential to the successful functioning of observatories. They also demonstrate the breadth and variety of interests and resources that were drawn into these networks, offering new ways of understanding and interpreting both observatory sites and museum objects.